Development and pilot‐testing of a Decision Aid for use among Chinese women facing breast cancer surgery - Au, Angel H.Y. (Health Expect, 2011)
Background  Women choosing breast cancer surgery encounter treatment decision‐making (TDM) difficulties, which can cause psychological distress. Decision Aids (DAs) may facilitate TDM, but there are no DAs designed for Chinese populations. We developed a DA for Chinese women newly diagnosed with breast cancer, for use during the initial surgical consultation. Aims  Conduct a pilot study to assess the DA acceptability and utility among Chinese women diagnosed with breast cancer. Methods  Women preferred the DA in booklet format. A booklet was developed and revised and evaluated in two consecutive pilot studies (P1 and P2). On concluding their initial diagnostic consultation, 95 and 38 Chinese women newly diagnosed with breast cancer received the draft and revised draft DA booklet, respectively. Four‐day post‐consultation, women had questionnaires read out to them and to which they responded assessing attitudes towards the DA and their understanding of treatment options. Results  The original DA was read/partially read by 66/22% (n = 84) of women, whilst the revised version was read/partially read by 74/16% (n = 35), including subliterate women (χ(2) = 0.76, P = 0.679). Knowledge scores varied with the extent the booklet was read (P1: F = 12.68, d.f. 2, P < 0.001; P2: F = 3.744, d.f. 2, P = 0.034). The revised, shorter version was graphically rich and resulted in improved perceived utility, [except for the ‘treatment options’ (χ(2 )=( )5.50, P = 0.019) and ‘TDM guidance’ (χ(2 )=( )8.19, P = 0.004) sections] without increasing anxiety (F = 0.689, P = 0.408; F = 3.45, P = 0.073). Conclusion  The DA was perceived as acceptable and useful for most women. The DA effectiveness is currently being evaluated using a randomized controlled trial.